Carbon fiber oxidation in combustion environments—Effect of flame chemistry and load on bundle failure. (June 2022) - Chávez-Gómez, Pablo; Pelzmann, Tanja; Zahlawi, Joanna; Laberge Lebel, Louis; Robert, Étienne
Abstract: Carbon fiber (CF)-based composites are susceptible to fire attack. In this work, we assess the effect of flame chemistry and load on the oxidation-induced failure of three polyacrylonitrile-based CFs with different tensile modulus. Traditional thermal analyses initially showed the influence of microstructure and heating rate on the oxidative behavior. Two different flame-based tests were implemented to address the CF behavior under true fire conditions. Filaments were inserted into a premixed methane/air flame. Subsequent scanning electron microscopy revealed prompt and heterogeneous fiber pitting even after short exposures ( t ≈ 0.5 s). The flame stoichiometry, characterized by the fuel/oxidizer ratio ( ϕ ), was varied to assess its effect on the CF bundle failure considering time-to-failure (TTF) as an indicator of fire resistance. The trends are similar for the three CF types. The stoichiometric flame ( ϕ = 1 . 0 ) yielded the least aggressive conditions despite being the hottest. Slightly faster bundle failures were caused by the fuel-rich configuration ( ϕ = 1 . 2 ), suggesting a contribution from  OH radicals. Higher tensile loads tended to reduce this difference. The enhanced aggressiveness of the fuel-lean condition ( ϕ = 0 . 7 ), i.e.,  oxygen-rich flame, was confirmed by a TTF at least 50% shorter than its stoichiometric counterpart. Moreover, we found a striking one order-of-magnitude difference in TTF between the high and standard/intermediate modulus CF bundles, regardless of  ϕ . The results highlight the critical importance of flame chemistry and fiber microstructure in the fire resistance of CF-based structures. Graphical abstract: Highlights: Carbon fibers (CFs) with different tensile modulus were exposed to flame attack. SEM observations revealed surface pitting even after short exposures (t = 0.5 s). The fire resistance of CF bundles was determined by the time-to-failure (TTF). High modulus CFs yielded one order-of-magnitude longer TTF vs. lower modulus CFs. Fuel-lean flames shortened the TTF by at least 50%  vs. stoichiometric conditions.